2009
DOI: 10.1097/bco.0b013e3181ae6abe
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment of non-malignant active and aggressive bone tumors

Abstract: Aggressive but nonmalignant bone tumors often pose a difficult therapeutic dilemma for orthopaedic oncologists. Intralesional surgery usually is the modality of choice to lessen the morbidity associated with a marginal or wide excision. With more aggressive tumors, such as giant cell tumor of bone, chondroblastoma or aneurysmal bone cysts, high recurrence rates after curettage alone present a challenge to the surgeon. Adjuvant therapies provide an additional means of clearing the cavity of tumor cells after ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…However, the management protocol was similar in all patients. Finally, the time for follow-up in our study was relatively short 3.4 years, although various studies have shown that most of the local recurrences occur before 2 years, 6,11,14,32,42 there have been reports of late recurrence of GCT. 25,43 Also, degenerative changes in joint may take a longer time to develop.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, the management protocol was similar in all patients. Finally, the time for follow-up in our study was relatively short 3.4 years, although various studies have shown that most of the local recurrences occur before 2 years, 6,11,14,32,42 there have been reports of late recurrence of GCT. 25,43 Also, degenerative changes in joint may take a longer time to develop.…”
Section: Discussionmentioning
confidence: 76%
“…The use of high-speed bur is accepted worldwide by all surgeons and it has shown to decrease recurrence after curettage to 25%. 6,7,18,23,24 Algawahmed et al in their metaanalysis compared recurrence rates in GCT following intralesional curettage and high-speed burring with a cohort of patients who underwent the same procedure plus a chemical or thermal adjuvant. They concluded that meticulous surgical technique including high-speed burring and not the use of adjuvants is the most important step in reducing recurrence rates in GCT of bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adjuncts include phenol, liquid nitrogen and bone cement/PMMA, which is the most widely used adjunct either in combination or in isolation. Polymethyl methacryllate is formed by an exothermic reaction and induces thermal tumour necrosis and also hypoxic tumour necrosis induced by its monomer (16). Balke et al showed that statistically the use of bone cement significantly decreased the recurrence rate by a factor of eight when compared to high-speed burring used in isolation (13).…”
Section: Discussionmentioning
confidence: 99%